Mitigation of parasitic leakage current in indoor perovskite photovoltaic modules using porous alumina interlayer - Jeon, Gyeong G.; Lee, Da Seul; Choi, Min Jun; Seo, You Hyun; Huang, Shujuan; Kim, Jong H.; Shin, Seong Sik; Kim, Jincheol (EcoMat, 2024)
Indoor photovoltaics are limited by their inherently low-photogenerated carrier density, leading to heightened carrier recombination and adverse leakage currents compared with conventional solar cells operating under 1 sun condition. To address these problems, this work incorporates a porous insulating interlayer (Al2O3) in perovskite devices, which effectively mitigates recombination and parasitic leakage current. A systematic investigation of the relationship between shunt resistance, photocarrier generation, and recombination at different light intensities demonstrates the effectiveness of the alumina interlayer in perovskite solar cells under low-light conditions. Moreover, the practicability of the alumina interlayer was demonstrated through its successful implementation in a large-area perovskite solar module (PSM). With bandgap engineering, the optimized PSM achieves a remarkable power conversion efficiency of 33.5% and a record-breaking power density of 107.3 μW cm−2 under 1000 lux illumination. These results underscore the potential of alumina interlayers in improving energy harvesting performance, particularly in low-light indoor environments. (Figure presented.).
Keywords: alumina interlayer; low-light intensity; parasitic leakage current; perovskite solar cells; photovoltaic devices